Antibacterial Effect of Black Pepper Petroleum Ether Extract against Listeria monocytogenes and Salmonella typhimurium - Wenxue Chen; Hui Tang; Ningxin Jiang; Qiuping Zhong; Yueying Hu; Haiming Chen; Weijun Chen (Journal of Food Quality)
The aim of the present study was to evaluate the antibacterial effect of black pepper petroleum ether extract (BPPE) against Listeria monocytogenes ATCC 19115 and Salmonella typhimurium ATCC 14028. The results showed that the BPPE had a strong antimicrobial activity against L. monocytogenes and S. typhimurium, and 2-methylene-4,8,8-trimethyl-4-vinyl-bicyclo[5.2.0]nonane (9.36%) and caryophyllene oxide (4.85%) were identified as the two primary components of BPPE. The ability of cells to break down hyperoxide was decreased, and the activities of POD and CAT were inhibited. The activities of key metabolic enzymes shed some light on the biochemical mechanism of aglycon cell growth inhibition, indicating that the energetic metabolism of L. monocytogenes and S. typhimurium was markedly influenced by the BPPE. The contents of key organic acids varied significantly, resulting in remarkable abnormalities in the energetic metabolism of L. monocytogenes and S. typhimurium. Thus, the consecution of energetic metabolism was destroyed by the BPPE, which contributed to metabolic dysfunction, the suppression of gene transcription, and cell death.